2017
DOI: 10.14245/kjs.2017.14.3.89
|View full text |Cite
|
Sign up to set email alerts
|

Single Stage Posterior Approach for Total Resection of Presacral Giant Schwannoma: A Technical Case Report

Abstract: The neurogenic tumor of frequent occurrence in the presacral area is a schwannoma. Giant presacral schwannoma has a risk for anterior surgical approach because of its massive size and proximity to abundant vascularity of presacral region. We report a single stage posterior approach for total resection of a giant presacral schwannoma. A 40-year-old female patient experienced left buttock pain and tingling sensation at left S1 dermatome. Magnetic resonance imaging showed that the presacral huge mass at S1–3 leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…To reduce the complications of conventional VCR, Suk et al [ 21 ] described a posterior VCR (PVCR) technique. Nevertheless, there is still a risk of complications with PVCR [ 3 , 14 , 18 ]. The incidence of complications after PVCR was reported to range from 40% to 67% [ 6 , 10 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the complications of conventional VCR, Suk et al [ 21 ] described a posterior VCR (PVCR) technique. Nevertheless, there is still a risk of complications with PVCR [ 3 , 14 , 18 ]. The incidence of complications after PVCR was reported to range from 40% to 67% [ 6 , 10 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adult long spinal instrumented fusion may be necessary for various conditions such as degenerative lumbar scoliosis, sagittal imbalance, transition syndrome, and revision cases to alleviate back pain and to achieve balance and stabilization of the fused segments. 7 However, stress concentration on the proximal junction after posterior long spinal instrumented fusion, from the thoracolumbar spine to S1 or the pelvis, has demonstrated several junctional changes: PJF including fractures, proximal junctional kyphosis, junctional disc rupture, and junctional spinal stenosis. [8][9][10][11] Several previous studies have reported various risk factors associated with PJF, known risk factors include older age, osteoporosis, female sex, high UIV angle, preoperative kyphosis adjacent to the UIV, inadequate implant systems, the level of the UIV, preoperative hyperkyphotic thoracic alignment, sagittal imbalance, and acute correction of sagittal imbalance.…”
Section: Discussionmentioning
confidence: 99%
“…However, direct removal of OPLL has a high risk of complications such as dural tear and neurologic deficit, etc 12,24,26) . Diverse results of surgical techniques have been reported 2,5,8,[13][14][15]25) . Posterior approach is considered to be relatively safe, but the guidelines for surgical treatment have not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…This is because of the high risk of complication related with surgery 19) . Different results of various surgical approaches and techniques have been reported 2,8,[13][14][15]25) . Posterior approach is considered to be relatively safe, although definitive results of an optimal surgical method have not been presented.…”
Section: Introductionmentioning
confidence: 99%